INTERNALISASI NILAI MERDEKA BELAJAR DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DI MASA PANDEMI COVID-19 - Ranu Suntoro; Hendro Widoro (Jurnal Mudarrisuna: Media Kajian Pendidikan Agama Islam, 2020)
The COVID-19 pandemic which has a significant influence on aspects that surround the lives of the people, is no exception to the aspects of formal education. The policy of physical application diverts by the government resulting in the application of learning from home through online at every level of the education unit. Therefore we need assistance in several ways, it is proposed that learning follows with its assessment, so that education services remain safe, concentrated on Islamic subjects that are the object of this study. The 4 main principles of the independent learning policy launched by the Minister of Education and Culture of the Republic of Indonesia in 2019 then became fresh education for teachers to open horizons and to address problems that occurred. Therefore this article describes the internalization of the value of independent learning in PAI learning during the COVID-19 pandemic that was implemented at SDN Rejosari 3. This study uses qualitative, data associations using participatory participation, studies, and interviews. In this study there are 2 aspects of internalization, namely; the basic idea of internalization that adheres to the normative aspects, namely the law and circular of the education office, as well as the subjectivity view of the teacher towards a free learning policy, namely the value of flexibility contained therein. As for internalization in the form of learning implementation plans, literacy awareness and social character and assessment patterns.